Larvae of Hydropsyche angustipennis (Trichoptera, Hydropsychidae) as indicators of stream contamination by heavy metals in Łódź agglomeration - Tszydel, Mariusz; Markowski, Marcin; Majecki, Janusz (Zootaxa, 2016)
A biomonitoring technique was employed to assess metal contamination of several degraded urban streams in the Łódź agglomeration. Presence of heavy metals (Zn, Cu, Fe, Cd, Pb, Cr, was determined in whole bodies of Hydropsyche angustipennis larvae. Larvae of H. angustipennis were the only caddisflies living in most of investigated streams. These metals as well as other environmental variables were investigated in sediments or free waters of urban streams and in a stretch of a similar size of the Grabia River (reference site), outside the city but still in the vicinity of the Łódź agglomeration. The results of our research demonstrated different levels of contamination of urban streams as well as a correlation between environmental and larval tissue concentrations of heavy metals. Significant differences among sites were observed for metal concentrations in H. angustipennis larval bodies and larval responses to metals were time specific. The highest concentration of heavy metals was observed during the spring months. Differences were evident among various heavy metal levels in the bodies of larvae collected from different streams and at different sampling stations in the same stream.